An Inertia Correction Scheme for Hydrodynamic Lubrication Problems - Ozen, Seyhan; Azeloglu, C. Oktay (WILEY, 2025)
A new simplified numerical approach for accurately calculating the bearing pressure distribution in one-dimensional hydrodynamic lubrication problems, particularly including convective fluid inertia and film discontinuities, is presented. The method proposes a simple inertia correction scheme using a non-uniform finite difference method based on the Reynolds equation. Two possible approaches to estimating the pressure correction due to fluid inertia are discussed: the Bernoulli effect and the averaged inertia. The results obtained for various operating conditions, especially by employing the average fluid inertia method, are found to be almost identical to the full Navier-Stokes (CFD) results and are more generalized. The proposed method may provide extremely fast calculation with accuracy.
Keywords: film discontinuity; fluid inertia; hydrodynamic lubrication; non-uniform grid; Rayleigh step bearing; REYNOLDS-EQUATION; FORCES; Computer Science; Mathematics; Mechanics; Physics